Genes involved in the WNT and vesicular trafficking pathways are associated with melanoma predisposition. Issue 9 (24th October 2014) - Ibarrola‐Villava, Maider; Kumar, Rajiv; Nagore, Eduardo; Benfodda, Meriem; Guedj, Mickael; Gazal, Steven; Hu, Hui‐Han; Guan, Jian; Rachkonda, P. Sivaramakishna; Descamps, Vincent; Basset‐Seguin, Nicole; Bensussan, Armand; et al.
<x xml:space="preserve">Abstract</x> Multifactorial predisposition to melanoma includes genes involved in pigmentation, immunity and DNA repair. Nonetheless, missing heritability in melanoma is still important. We studied the role of 335 candidate SNPs in melanoma susceptibility by using a dedicated chip and investigating 110 genes involved in different pathways. A discovery set was comprised of 1069 melanoma patients and 925 controls from France. Data were replicated using validation phases II (1085 cases and 801 controls from Spain) and III (1808 cases and 1894 controls from Germany and a second set of Spanish samples). In addition, an exome sequencing study was performed in three high‐risk French melanoma families. Nineteen SNPs in 17 genes were initially associated with melanoma in the French population. Six SNPs were replicated in phase II, including two new SNPs in the WNT3 (rs199524) and VPS41 (rs11773094) genes. The role of VPS41 and WNT3 was confirmed in a meta‐analysis (3940 melanoma cases and 3620 controls) with two‐side p values of 0.002, (OR = 0.86) and 4.07 × 10−10 (OR = 0.80), respectively. Exome sequencing revealed a non‐synonymous VPS41 variant in one family that was shown to be strongly associated with familial melanoma (OR = 4.46, p = 0.001) in an independent sample of 178 melanoma families. WNT3 belongs to WNT pathway known to play a crucial role in melanoma, whereas VPS41 regulates vesicular trafficking and is thought to play a role in pigmentation. Our work identified two new pathways involved in melanoma predisposition. These results may be useful in the future for identifying individuals highly predisposed to melanoma.